Identifikasi Pengelolaan Destinasi Pariwisata Di DPD Segoro Kidul Kabupaten Bantul - Fifiyanti, Debby; Muhammad Luqman Taufiq (Yayasan Literasi Sains Indonesia, 2022)
The tourism development of Bantul Regency is planned based on the Bantul Regency Regional Regulation Number 11 of 2020 concerning Amendments to the Bantul Regency's Regional Regulation Number 18 of 2015 concerning the 2015-2025 Regional Tourism Development Master Plan. The rapid development of tourism in the South Coast Region of Bantul Regency is certainly very helpful in increasing regional original income and can also improve the community's economy. One of the important things in tourism development and development is the management system of a tourism destination. Based on the Regional Regulation of Bantul Regency Number 18 of 2015 concerning the Master Plan of Regional Tourism Development for 2015-2025, Bantul Regency has 5 (five) Regional Tourism Destinations (DPD), one of which is DPD Segoro Kidul which has tourism potential that can be developed. With this potential, there must be good management so that the existing tourist attraction components can be used as tourism support. Components of tourist attraction and management of tourist attractions by using the concept of a tourist attraction component (4A) which includes attraction (tourist attractions), accessibilities (access), aminities (facilities), and ancillary service (institutional). The method used in this study uses a qualitative approach. Data collection techniques were carried out by direct interviews, observation, and documentation. Identification of the management of tourist destinations in DPD Segoro Kidul with three stages, namely reducing data, presenting data and drawing conclusions. The results of this study indicate that component 4A has been realized in this area to be used as tourism products and supporting facilities in tourism processing in DPD Segoro Kidul. Coastal tourism destinations are still the leading product in this area, accessibility and amenities are also one of the factors that affect connectivity between tourism destinations, and stakeholder involvement is still an important actor in the management of a tourist destination